Nested Sequential Procedures - Longley, John; Normann, Dag (Higher-Order Computability, 2015)
In this chapter, we study in depth the nested sequential procedure (NSP) model which we introduced briefly in Subsection 3.2.5. The point of view we shall adopt is that NSPs offer an abstract formulation of an underlying concept of ‘algorithm’ that is common to both Kleene computability (as studied in the previous chapter) and Plotkin’s PCF (the subject of the next chapter). We shall consider NSPs both as forming a self-contained model of computation in their own right, and as a calculus of algorithms that can be interpreted in many other (total and partial) models.